Caregiver burden and the associated factors in the family caregivers of patients with schizophrenia - Farnaz Rahmani; Fariborz Roshangar; Leila Gholizadeh; Elnaz Asghari (Nursing Open, 2022)
Abstract Aim Our study aimed to investigate the caregiving burden and its associated factors in family caregivers of patients with schizophrenia. Design Correlational study. Method Using the convenience sampling method, 215 caregivers were recruited from outpatient clinics affiliated with a tertiary referral psychiatric hospital in Iran. The caregiving burden was measured by the Zarit Burden Interview (ZBI‐22), and associations between caregiving burden and potential factors were examined using multiple regression analysis. We used the STROBE checklist to report the results. Results Family caregivers of patients with schizophrenia reported a high level of caregiving burden, with 38.2% of the caregivers perceiving severe burden relating to their role. In the regression analysis, age, gender, educational level, income, job loss due to caregiving, relationship with patient, disease duration and frequency of caregiving were statistically significant predictors of caregiving burden. The regression model explained 54.4% of the variance of caregiving burden.